COMPARATIVE ANALYSIS OF THE CHRONIC VIRAL HEPATITIS B MARKERS PREVALENCE IN HIV-INFECTED AND CONDITIONALLY HEALTHY RESIDENTS OF HO CHI MINH CITY - Yu. V., Ostankova; D. E., Valutite; E. B., Zueva; E. N., Serikova; A. N., Shchemelev; Huynh, Hoang Khanh Thu; A. V., Semenov; Areg A., Totolian (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
COMPARATIVE ANALYSIS OF THE CHRONIC VIRAL HEPATITIS B MARKERS PREVALENCE IN HIV-INFECTED AND CONDITIONALLY HEALTHY RESIDENTS OF HO CHI MINH CITYThe prevalence of chronic HBV infection, as measured by the hepatitis B surface antigen (HBsAg) prevalence, is 8-20% in the general population and 31-54% in the high-risk urban population in Vietnam. Vietnam is currently one of the countries with the highest mortality rates from liver cancer associated mainly with HBV infections. One of CHB natural progression forms is presented by occult hepatitis B infection (OBI), which is characterized by HBV DNA persistence in liver tissue and extremely low HBV DNA concentration with undetectable HBsAg level in peripheral blood. One of the tasks required is to estimate the prevalence of CHB and OBI among conventionally healthy people and in risk groups (for example, among HIV-infected individuals). The analysis of the overall prevalence of serological markers showed that among the conditionally healthy individuals and HIV-infected persons HBsAg were detected in 12.3% and 9.49% of individuals, respectively. The prevalence of HBV DNA in the examined groups (26.95% and 32.58%) exceeds the previously published prevalence rates for the virus in the population in region. Our results of HBV genotyping indicate that HBV genotype B dominates in residents of Ho Chi Minh City, followed by genotype C. However, HBV genotype B occurrence frequency among HBsAg-positive individuals is much higher, than the corresponding frequency among OBI patients. In addition, in our study, a significant number of C5 subtype samples (3.74% conditionally healthy persons, 4.34% HIV-infected individuals) were identified among HBsAg-negative samples. The results obtained in this work demonstrate a high prevalence of CHB/OBI in the region and indicate the need for further large-scale studies of HBV in order to improve strategies for disease control and prevention in the Vietnam.